Association between lactate-to-albumin ratio and short- and long-term mortality in critically ill patients with ischemic stroke: a retrospective analysis of the MIMIC-IV database: Lactate-to-Albumin Ratio and Mortality in Ischemic Stroke - Qin, Sisi; Xiao, Jijie; Yuan, Shiqi; Zhang, Huitao; Liu, Yang; Li, Ningjun; He, Songjin; Kou, Li (Journal of Medical Biochemistry, 2025)
Background: Stroke is a major cause of disability and cognitive deficits, with ischemic stroke (IS) being the most prevalent type, especially in critically ill patients in intensive care units (ICUs). The lactate-to-albumin ratio (LAR) has emerged as a potential predictor of disease outcomes, but its association with short- and long-term mortality in critically ill IS patients is unclear. Methods: This study analyzed data from 894 critically ill IS patients from the MIMIC-IV database, categorized into LAR tertiles. Clinical endpoints included ICU, hospital, and 30- and 90-day all-cause mortality. Survival differences were assessed using Kaplan-Meier analysis. Cox proportional-hazards regression models and restricted cubic spline (RCS) analysis evaluated the association between LAR and mortality outcomes. Subgroup analyses examined the modifying effects of clinical characteristics on LAR’s predictive value. Results: The ICU, hospital, 30-, and 90-day mortality rates were 15.0%, 22.3%, 28.2%, and 36.1%, respectively. Higher LAR levels were associated with reduced survival times and increased mortality risks in all endpoints. Multivariable Cox models confirmed LAR as an independent predictor of 30- and 90-day mortality. RCS analysis indicated a linear relationship between LAR and ICU mortality (P = 0.109), and a non-linear association with hospital (P = 0.005), 30-day (P < 0.001), and 90-day mortality (P < 0.001). Subgroup analyses highlighted significant interactions for respiratory failure and GCS. Conclusion: LAR is a robust predictor of short- and long-term mortality in critically ill IS patients, offering clinicians a valuable tool for risk stratification and decision-making.